Pengaruh Kemudahan Penggunaan E-Wallet dan Gaya Hidup Cashless terhadap Perilaku Konsumtif Mahasiswa - Bilqis Agustina Windiary; Sri Trisnaningsih (Forum Kerjasama Pendidikan Tinggi, 2026)
The development of financial technology has driven the increasing use of e-wallets and the adoption of a cashless lifestyle among students. The ease of transactions offered by digital payments can influence user consumption patterns. This study aims to analyze the effect of e-wallet ease of use and a cashless lifestyle on the consumer behavior of Accounting students at UPN Veteran East Java. This study uses a quantitative approach with a survey method. Data were obtained by distributing questionnaires to 77 respondents selected using a simple random sampling technique. Data analysis was performed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with the help of the SmartPLS 4 application. The results showed that e-wallet ease of use had a positive and significant effect on student consumer behavior with a t-statistic of 2.741 and a p-value of 0.0006, and a cashless lifestyle also had a positive and significant effect with a t-statistic of 5.830 and a p-value of 0.000. The R-square value of 0.364 indicates that 36.4% of the consumer behavior variables are explained by this model. The easier an e-wallet application is to use, the higher the tendency of students to engage in consumption activities. A cashless lifestyle has also been shown to have a positive and significant impact on consumer behavior. The ease, speed, and practicality of cashless transactions encourage students to make more unplanned purchases. The findings of this study indicate that the use of digital payment technology and changes in societal transaction patterns play a role in shaping student consumption behavior in the digital era. This study provides an empirical contribution in expanding the study of student consumer behavior in the digital payment era by analyzing the influence of e-wallet ease of use and a cashless lifestyle. The research findings are expected to serve as a reference for further research and for stakeholders interested in improving digital financial literacy.